(untitled) (Indian Journal of Animal Production and Management, 2013)
An investigation was carried out on 18 numbers of new born Yak calves of either sex to study the effect of raising the calves under three feeding systems on body weight, body measurements and physiological responses. The calves were divided into three groups and were placed under three rearing systems: Natural suckling (T1), Milk replacer with bottle feeding (T2) and whole milk with bottle feeding like foster mother (T3). A milk replacer was prepared with conventional feed ingredients containing 22 per cent CP and was offered to the calves under T2 group. Calves under T1 were allowed to suckle ad lib. mothers’ milk two times a day and the calves under T3 were offered yak whole milk as per body weight requirement. During three months of experimental period, no significant change in body weight, body measurements and physiological responses (pulse, respiration and rectal temperature) were observed among the groups. This study shows that yak calves can be reared under milk replacer feeding containing 22 per cent CP from birth to three months of age without affecting the growth, body measurements and physiological responses.